Analisis Financial Distress pada Perusahaan Konstruksi BUMN Karya - Yang Gisella Yulialistika Esfandiatri (Syntax Idea)
This study aims to measure the performance and financial health of the BUMN Karya Construction Company based on an analysis of financial reports from 2019 to 2022. This research is also intended to determine increases or decreases in financial performance and even financial distress. This study examines financial problems in 5 (five) BUMN Karya companies, including PT. Adhi Karya, PT. Waskita Karya, PT. Wijaya Karya, PT. Pembangunan Perumahan and PT. Hutama Karya. Financial performance measurement analysis based on Financial Ratio Analysis and Discriminant or Financial Distress Prediction Models include the Altman Z-score Model, the Springate Model, the Grover Model and the Zmijewski Model. The research will be measured based on the individual analysis of each company and the comparative analysis of the 5 (five) BUMN Karya. The results of the research based on analysis of financial ratios and 4 (four) financial distress models obtained values of 50% to 100%, so that it can be concluded that 5 (five) BUMN Karya companies are experiencing financial distress or financial difficulties and are on the verge of bankruptcy. While the research results are based on the calculation of financial ratios where the average state-owned company works, the majority of its assets come from debt but still have sufficient cash to pay off its debts. The conclusion from the results of this study can be used as an early warning related to the company's financial condition, so that it can be planned to develop company policies and strategies for better financial performance and avoid financial distress.